Russia at Play : Leisure Activities at the End of the Tsarist Era - McReynolds, Louise, 1952- (Book collections on Project MUSE., 2003)
"Leisure-time activities, McReynolds finds, allowed Russians to re-create themselves, to develop a modern identity that allowed for different senses of the self depending on the circumstances. The society that spawned these impulses would disappear in Russia for decades under the combined blows of revolution, civil war, and collectivization, but questions of personal identity are again high on the agenda as Russia makes the transition from a collectivist society to one in which the dominant ethos remains undefined."--Jacket